A Comprehensive review on Butea monosperma (Lam.) Kuntze - Burli, D. A.; Khade, A. B. (Pharmacognosy Reviews)
Butea monosperma (Lam.) is an indispensable tree. Tribals use its flowers and young fruits. The plant is used in Ayurvedic, Unani and Siddha medicine for various ailments. Almost all the parts of the plant namely root, leaves, fruit, stem bark, flowers, gum, young branches are used as medicine, food, fibre and for other miscellaneous purposes such as fish poison, dye, fodder, utensils, etc. About 45 medicinal uses are associated with the plant and out of these claims almost half the number of claims have been scientifically studied and reported. These observations are noteworthy for further studies on modern scientific lines.
Keywords: Butea monosperma; traditional uses; scientific reports; review